Application of Functional Nanomaterials in Aesthetic Art and Industrial Design Concept. (16th August 2022) - Gong, Da; Li, Zhenghang; Song, Yuyan; Han, Jiaheng
Abstract : Industrial design (ID) refers to industrial product design based on engineering, aesthetics, and economy. Traditional industrial design refers to the creative activities of designing and designing products produced by industrial means to make the best match with the environment and the people who use them. This paper aims to study how to analyze and study the application of aesthetic art, that is, the concept of industrial design, based on functional nanomaterials, and this paper describes the electrospinning technology. This paper puts forward the problem of the industrial design concept, which is based on design aesthetics. Therefore, this paper focuses on the development of industrial design and related elements. The application of functional nanomaterials in industrial design is designed and analyzed. The experimental results show that when the acid soaking time is 4∼12 days, the mechanical strength of the nanofiber membrane is 7∼9 MPa. Compared with the untreated nanofiber membrane, it increased by 25.4%∼48.8%, and the ductility decreased from 81.5% to 44.1%.